Efficiency of inoculation methods for genotypes selection in corn ear rot disease studies - Araujo, Sabrina Helena; Júnior, Oelton Ferreira; Viteri, Luis Oswaldo; Aguiar, Raimundo Wagner; Oliveira, Eugênio Eduardo; Santos, Gil Rodrigues (Revista de Ciencias Agrícolas, 2022)
The identification of resistance of plants to pathogens is crucial for the development of hybrids by breeding programs. To achieve that, it is of great relevance to establish effective inoculation methods for characterizing genotypes with adequate plant resistance levels. Several inoculation methods have been investigated in the search for resistance to corn ear rot disease. However, studies evaluating different corn genotypes cultivated under Neotropical field conditions remain unexplored. Here, we compared three inoculation methods (i.e., aspersion, injectable, and natural) of Fusarium verticillioides in corn ears, and evaluated disease severity and grain yield of 10 corn genotypes. The experiments were conducted in two consecutive experimental corn crop (i.e., 2015 and 2016) seasons located in cities with different environmental temperatures and belonging to different Brazilian states (i.e., Gurupi – Tocantins State, Itumbiara – Goiás State, Planaltina – Brazilian Federal District, and Toledo – Paraná State). We evaluated the mass of 1000 grains and the severity of the disease. Regarding the disease severity, our results showed that the artificial inoculation was more efficient in the regions of Planaltina and Toledo, not affecting grains’ mass in these localities. The severity of disease on the conditions of Toledo was similar for the ten genotypes. However, it was possible to identify two contrasting genotypes since P4285H (low severity) and 32R48YH (medium severity) exhibited significantly more disease symptoms in all other regions. Although the differences regarding the efficiency of inoculation methods are more evident in regions with milder temperatures, the results showed that the characterization of genotypes susceptible to the pathogen is more efficient in regions with higher temperatures.